Qt5 Python GUI Programming Cookbook: Building Responsive and Powerful Cross-Platform Applications with Pyqt - Harwani, B. M (Packt Publishing, Limited, 2018)
QT5 Python GUI Programming Cookbook will guide you from the very basics of creating a fully functional GUI application using PyQT with only a few lines of code. Each recipe adds more widgets to the GUIs we are creating. You will learn how easy it is to get started and you might be surprised how advanced you can become in just a short time of coding.